2022
DOI: 10.1038/s41598-022-23153-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Japanese Parenting Style Scale and examination of its validity and reliability

Abstract: Parenting is an essential factor affecting child development. Therefore, several studies have focused on individual differences in parenting (i.e., parenting styles). However, there exist only a few useful scales in Japan, especially for parents who have preschool children. Therefore, a new scale for assessing parenting styles in Japan, based on the traditional theoretical framework, was developed, and examined for its validity and reliability. In Study 1, 82 original items were constructed and 1236 parents wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The Seventh National Census of China in 2020 reported rural and urban differences in population distributions (e.g., percentage of citizens aged 25–35 years with college or higher degree: urban 27.1% VS rural 3.2%; families with only one child: urban 54.3% VS rural 38.7%; income per capita: urban 3,529 RMB VS rural 1,335 RMB; marriage rate: urban 70.9% VS rural 73.9%) [ 46 ]. In addition, previous evidence also indicated that family income [ 51 ], parental age [ 51 , 52 ], marital status [ 53 ], number of children in the household [ 54 , 55 ], child age [ 52 , 56 ], and help from other caregivers [ 57 ] were associated with parenting styles. Therefore, differences in parental age, monthly income per capita (CNY), marital status, number of children, age of the target child, and whether they had other caregivers caring for the child between rural and urban parents were affected by rural and urban residency (and hence, they were not confounders [ 58 ]) and may explain the rural–urban differences in parenting and parenting service utilization and needs, and hence were operationalized as mediators in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The Seventh National Census of China in 2020 reported rural and urban differences in population distributions (e.g., percentage of citizens aged 25–35 years with college or higher degree: urban 27.1% VS rural 3.2%; families with only one child: urban 54.3% VS rural 38.7%; income per capita: urban 3,529 RMB VS rural 1,335 RMB; marriage rate: urban 70.9% VS rural 73.9%) [ 46 ]. In addition, previous evidence also indicated that family income [ 51 ], parental age [ 51 , 52 ], marital status [ 53 ], number of children in the household [ 54 , 55 ], child age [ 52 , 56 ], and help from other caregivers [ 57 ] were associated with parenting styles. Therefore, differences in parental age, monthly income per capita (CNY), marital status, number of children, age of the target child, and whether they had other caregivers caring for the child between rural and urban parents were affected by rural and urban residency (and hence, they were not confounders [ 58 ]) and may explain the rural–urban differences in parenting and parenting service utilization and needs, and hence were operationalized as mediators in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Research focusing on individual differences in parenting style and emotional and behavioural adjustment highlights that parenting is an essential factor affecting child development [14] . For example, positive parent-child support early in life can shield against various forms of difficulties, as well as have a positive impact on all areas of development, including language and communication, executive function, self-regulation, relationships with siblings and peers, academic achievement, mental and physical health [15] .…”
Section: Introductionmentioning
confidence: 99%